His Name Was Seth Rich [Part 1: Introduction] - Brunet, Christopher (2022)
'There are a thousand and one gates leading into the orchard of mystical truth. Every human has his own gate. We must never make the mistake of wanting to enter the orchard by any gate but our own.'